Abstracting and Structuring Web Contents for Supporting Personal Web Experiences - Firmenich, Sergio Damián (2016)
This paper presents a novel approach for supporting abstraction and structuring mechanisms of Web contents. The goal of this approach is to enable users to create/extract Web contents in the form of objects that they can manipulate to create Personal Web experiences. We present an architecture that not only allows the user interaction with individual objects but also supports the integration of many objects found in diverse Web sites. We claim that once Web contents have been organized as objects it is possible to create many types of Personal Web interactions. The approach involves end-users and developers and it is fully supported by dedicated tools. We show how end-users can use our tools to identify contents and transform them into objects stored in our platform. We show how developers can use of objects to create Personal Web applications.